Comparing efficacy and tolerability of ibuprofen and paracetamol in fever. Issue 2 (February 1996) - McIntyre, J; Hull, D
Abstract : The purpose of this study was to compare antipyretic activity and evaluate tolerability of ibuprofen and paracetamol suspension in the treatment of febrile children. It was designed as a double blind, parallel group, multiple dose study comparing ibuprofen (20 mg/kg/24 hours) with paracetamol (50 mg/kg/24 hours) given at six hourly intervals for a maximum of 12 doses. Children on paediatric wards between the ages of 0.2 and 12 years, with fever as defined by an axillary temperature > or = 37.5 degrees C, were included. The main outcome measures were: change in axillary temperature; palatability of medication; changes in irritability and clinical condition; overall efficacy at the end of treatment; and number and nature of adverse events. The mean temperature change from baseline at four hours was -1.8 degrees C and -1.6 degrees C in ibuprofen and paracetamol groups respectively. In both groups: median palatability score was 'no reaction'; median irritability score at end point was 'not irritable'; median score for change in clinical condition was 'improved'; and median score for overall efficacy was 'good effect'. The proportion of patients experiencing adverse events was similar in both groups, the majority of events having doubtful or no relationship to therapy and being mild in severity. In conclusion, ibuprofen suspension was as effective and well tolerated as paracetamol in treatment of fever in young children.